The role of headmater to improve the quality of education in 4 state basic schools in kecamatan air kumbang - Rina Puspita Sari; Happy Fitria; Achmad Wahidy (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This study aims to determine and describe the role of school principals in improving the quality of education in SD Negeri 4 Air Kumbang District. This type of research is descriptive qualitative research. Data collection tools use documentation, interviews, observation and literature review. The data analysis technique uses descriptive qualitative analysis technique which consists of data collection, data reduction, data presentation, and conclusion and ferification. The results of the study state that the role of the principal in an effort to improve the quality of education in SD Negeri 4 Air Kumbang District is carried out by establishing a program to improve the quality of learning by implementing a program to improve the quality of learning into the vision and mission of the school then the principal communicates the vision and mission of the school related to standards quality of learning; and improving the quality of education through interpersonal teacher competence by encouraging teachers to improve their competence and teaching ability. The principal should improve his competence so that the role can have a maximum impact in efforts to improve the quality of education.